Formative assessment of teaching and learning in primary schools - Boyle﻿, Bill; Charles, Mane (Universiti Kebangsaan Malaysia, 2009)
﻿The context of this article is the education system in England and focuses on issues of accountability, measurement of standards, forms of assessment and the influence of those forms of assessment on pedagogy. These issues have major relevance to current international debate about teaching, learning and assessment. Since a National Curriculum was first introduced into England in 1988, the teaching of that curriculum has been assessed by a series of external (i.e., government produced) statutory summative tests at the end of key stages of a pupil 's schooling. Because of the English government's insistence on measuring schoolpelfomance through test outcomes, assessment has become equated with "testing" and is seen by teachers as a means of producing "scores" to measure standards rather than as a means to supply continuous information for teaching and to support learning. This article begins by looking at the origins of assessment for learning (AjZ) within the national curriculum and assessment context in England. The authors explained AjZS inclusion within the national policy and then described the survey data and school visit reports which provide empirical evidence for examining how AjZpolicy has been understood, implemented and whether it has changed pedagogy during the jive years since its national introduction.